Geochemistry and stable isotopes of the upper Campanian–lower Maastrichtian phosphorite‐bearing sequence, Central Jordan: Implications for their age, origin, and diagenesis. (18th November 2019) - Ahmad, Fayez; Baioumy, Hassan; Farouk, Sherif; Al‐Kahtany, Khaled; El‐Sorogy, Abdelbaset; Kirk, Jason
Abstract : Three major lithofacies have been described in Lajjun area, central Jordan, including the phosphorite and intercalated limestone of the Al‐Hisa Phosphorite Formation, as well as the Muwaqqar Chalk Marl Formation. 87 Sr/ 86 Sr isotopic data indicate a late Campanian age for the Al‐Hisa Phosphorite Formation, whereas the overlying chalk of the Muwaqqar Formation contains the lowest Maastrichtian planktic foraminiferal zone of Rugoglobigerina hexacamerata (CF8b). The phosphorites are of reworked origin as inferred from the homogeneous texture with lack of any concentric structure in the phosphatic pellets and the presence of bone fragments inside the phosphatic pellets, which are filled with phosphatic mud similar to the matrix of phosphatic pellet. They still reflect the original seawater rare‐earth pattern, as indicated from the similarity in their rare‐earth element (REE) concentration and patterns with seawater. Positive correlations between P2 O5 and Fe2 O3, TiO2 and K2 O, relatively high rare‐earth contents, and similarity in (Nd/Yb)SN ratio to the modern shallow seawater suggest a continental marginal depositional environment for the limestone and chalk facies. δ 13 C values are lower and more variable compared with the estimated global range of upper Campanian–lower Maastrichtian δ 13 C values in shelf and oceanic basins. This indicates a diagenetic effect on the δ 13 C isotopes and suggests that a significant proportion of carbonate ions could have been resulted from the organic carbon oxidation. Three third‐order depositional sequences matching with the global and regional sea‐level patterns are identified in the studied section based on vertical facies changes. The basal transgressive surface of each sequence is constantly characterized by a phosphatic horizon.